Peranan Humor terhadap Stres pada Remaja, dengan Kecerdasan Emosi sebagai Mediator - Erik Wijaya (Fakultas Psikologi Universitas Tarumanagara, 2018)
This study wanted to test the role of humor towards stress, with emotional intelligence as a mediator variable in adolescent. Research on humor in Indonesia has been done by involving the subject of a student who is writing a thesis, a student in the first year, a graduate student, as well as in middle adulthood. Based on this, researchers want to do further research to emphasize the role of humor with emotional intelligence as a mediator in adolescent. Research is done early in adolescent because the stressful sources of school and the peer group as part of the developmental tasks. Based on the results of this study found emotional intelligence has a role as a variable mediator of superiority humor and cognitive humor to stress. Keywords: Humor, emotional intelligence, stress, adolescent.